Toph beifong's metalbending academy ebook - Hicks, Faith Erin (Dark Horse Comics, LLC., 2021)
For some, perfection just isn't enough.Things are looking bright at the Beifong Metalbending Academy! But after all the adventures Toph's had with Aang, Sokka, Zuko, and Katara, the whole thing feels a bit dull. Luckily, Sokka and Suki come to visit and reintroduce some familiar faces from their wandering days. And while out and about to celebrate, Toph discovers something that just might put the sparkle back in her eye...Written by Faith Erin Hicks (The Adventures of Superhero Girl, The Nameless City) and drawn by Peter Wartman (Stonebreaker), with colors by Adele Matera and collaboration from Avatar: The Last Airbender animated series writer Tim Hedrick, this is the ultimate continuation of the hit animated series! Author: Faith Erin Hicks. Illustrator: Peter Wartman, Adele Matera.